Macroeconomic effects of China's financial policies - Kaiji Chen; Tao Zha (Federal Reserve Bank of Atlanta, 2018)
The Chinese economy has undergone three major phases: the 1978-97 period marked as the SOE-led economy, the 1998-2015 phase as the investment-driven economy, and the new normal economy since 2016. All three economies have been shaped by the government financial policies, defined as a set of credit policy, monetary policy, and regulatory policy. We analyze the macroeconomic effects of these financial policies throughout the three phases and provide the stylized facts to substantiate our analysis. The stylized facts differ qualitatively across different phases or economies. We argue that the impacts of China's financial policies work through transmission channels different from those in developed economies and that a regime switch from one economy to another was driven mainly by regime changes in financial policies.
Keywords: G1; G28; E5; O2; 330; marketized tools; regime change; growth; investment; capital intensity; local governments; regulations; shadow banking; debts; real estate; preferential credits; industrialization; SOEs; POEs; heavy and light sectors; monetary stimulus; trends and cycles